Electric vehicle by using modified topology of multilevel inverter - Rathinam, A. (MechAero Found. for Techn. Res. and Educ. Excellence, 2017)
This paper focused with extends the knowledge in studies and analysis of a new family of diode clamp multilevel inverter for electric vehicle application. The modified new diode clamp multilevel inverter concepts is related to reducing the components utilization, which has (n-1) switching devices, (n-3) clamping diodes, (n-1)/2 DC-link sources for achieving the same voltage level of traditional topologies. The proposed system is enhanced the voltage rating and reduce the total harmonics distortion in inverter output voltage. The switching scheme of Alternatively on Opposition Disposition pulse width modulation strategies is implemented to control multilevel inverter. The proposed system reduces the components utilization which has utilizes 45 of components for achieving the same level of voltage. The modified new diode clamp multilevel inverter is coupled with induction motor and its performance is validated with three phase induction motor for variable frequency drive. The inverter topologies performance has been investigated by prototype model. © 2017, MechAero Foundation for Technical Research & Education Excellence.